A practical microreactor for electrochemistry in flow - Watts, Kevin; Gattrell, William; Wirth, Thomas (Beilstein Journal of Organic Chemistry, 2011)
A microreactor for electrochemical synthesis has been designed and fabricated. It has been shown that different reactions can be carried out successfully using simple protocols.
Keywords: diaryliodonium compounds; electrochemistry; flow chemistry; microreactor

(untitled) - Yoshida, J.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Yoshida, J. (Electrochem. Soc. Interface, 2009)

Microreactors in Organic Synthesis and Catalysis - Wirth, T. (Wiley-VCH, 2008)

Flash Chemistry - Yoshida, J. (John Wiley & Sons, 2008)

(untitled) - Horii, D.; Atobe, M.; Fuchigami, T.; Marken, F. (Electrochem. Commun., 2005)

(untitled) - Horcajada, R.; Okajima, M.; Suga, S.; Yoshida, J. (Chem. Commun., 2005)

(untitled) - He, P.; Watts, P.; Marken, F.; Haswell, S. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Nagaki, A.; Togai, M.; Suga, S.; Aoki, N.; Mae, K.; Yoshida, J. (J. Am. Chem. Soc., 2005)

(untitled) - Suga, S.; Nagaki, A.; Tsutsui, Y.; Yoshida, J. (Org. Lett., 2003)

(untitled) - Yoshida, J. (Chem. Commun., 2005)

(untitled) - Kataoka, K.; Hagiwara, Y.; Midorikawa, K.; Suga, S.; Yoshida, J. (Org. Process Res. Dev., 2008)

(untitled) - Kajiyama, D.; Inoue, K.; Ishikawa, Y.; Nishiyama, S. (Tetrahedron, 2010)

(untitled) - Simms, R.; Dubinsky, S.; Yudin, A.; Kumacheva, E. (Lab Chip, 2009)

(untitled) - Amemiya, F.; Matsumoto, H.; Fuse, K.; Kashiwagi, T.; Kuroda, C.; Fuchigami, T.; Atobe, M. (Org. Biomol. Chem., 2011)

(untitled) - Tajima, T.; Fuchigami, T. (Chem.–Eur. J., 2005)

U.S. Patent - Beck, F.; Haufe, J.; Nohe, H. (Electrolytic condensation of carboxylic acids, 1974)

(untitled) - Kurihara, H.; Fuchigami, T.; Tajima, T. (J. Org. Chem., 2008)

(untitled) - Wirth, T. (Angew. Chem., Int. Ed., 2005)

(untitled) - Merritt, E. A.; Olofsson, B. (Angew. Chem., Int. Ed., 2009)

(untitled) - Peacock, M. J.; Pletcher, D. (Tetrahedron Lett., 2000)

(untitled) - Hoffelner, H.; Lorch, H. W.; Wendt, H. (J. Electroanal. Chem., 1975)

(untitled) - Katritzky, A. R.; Gallos, J. K.; Durst, H. D. (Magn. Reson. Chem., 1989)

(untitled) - Peacock, M. J.; Pletcher, D. (J. Electrochem. Soc., 2001)